The role of digitally-enabled employee voice in fostering positive change and affective commitment in centralized organizations. Issue 4 (1st October 2020) - Kim, Heewon; Leach, Rebecca
ABSTRACT: This study investigated the extent to which organizational structure and communication climate influence employee voice and concomitant outcomes. Given the prevalent use of digital technologies, we examined two discrete types of employee voice: identifiable, in-person voice vs. anonymous, digitally-enabled voice . Findings demonstrated that (a) organizational centralization was negatively linked to freedom of speech; (b) freedom of speech increased employee voice both at work and through anonymous social media, and (c) both types of voice had positive relationships with organizational change, which subsequently enhanced commitment. Our study advances employee voice scholarship by (a) highlighting the significance of communication climate and the efficacy of digitally-enabled anonymous voice, and (b) proposing employee voice as a multidimensional construct that encompasses content, identifiability, and modality.